Development, Labour Relations and Gender in Papua New Guinea - Fahey, Stephanie (The Australian journal of anthropology, 1986)
This paper examines the relationship between ‘subsistence’ production, simple commodity production and wage labour and the different effects this relationship has on males and females. The peri-urban village of Siar, located a few kilometres north of Madang town in Papua New Guinea, is used as a case study. It is argued that the village as a social group is dependent on wage labour for its reproduction and hence is proletarianized. As part of the proletarianization process, married women in the village have become doubly subordinated: to capital and to men.